Production relations and class conflict in a mine in southern Peru: Atalaya - Orlove, Benjamín Sebastián (1985)
Many people who have written about mines, be they journalists, political analysts or social scientists, have highlighted the high level of class conflict within them (Godoy 1985). Those who have entered a mine have come away with vivid visual images that make this description more relevant. This article examines a particular mine, Atalaya, located in the province of Espinar, department of Curso (Peru), at a specific time: November 1972. The mine is presented within several frameworks (systems) related to each other.